Структурно-фазовые превращения при формировании алмазного вольфрамсодержащего композита при высоких давлении и температуре - Быков, А.И.; Тимофеева, И.И.; Олейник, Г.С.; Пасичный, В.В.; Остапенко, В.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The results of research by the methods of X-ray and electronic microscopy analysis of transformations are presented for powder composition (UDD +WO₃) at pre-annealing in the environment of hydrogen in an interval 700-900 °С, and also at Р=7,7 GPa, Т=1400 = 1700 °С sintering
of composition after annealing. It is rotined that in the environment of hydrogen reduction of WO₃
passes through the stages of forming of dioxide and tungsten oxicarbide, and then formation of
tungsten carbides (W₂С and WС). At sintering of composition after hydrogen treatment the dispersion of carbides particles passes, and at Т = 1600 °С transformation of diamond → graphite passes
in surroundings of such particles.